Pengembangan Assessment for Learning (AfL) melalui Lesson Study pada Praktik Pemesinan SMK Sesuai Kurikulum 2013 - Endri Triwiyono (Department of Mechanical Engineering Education, 2017)
The aim of this research is to: (1) develop an assessment for learning (AFL), and (2) verify the effectiveness of the AFL through lesson study approach on machining practice in SMK. The research was a research and development with Borg & Gall's modified R&D model which comprised of 3 phase: development, small scale test, and large scale test. The research subjects were the students and teachers of machining program at SMK 2 Depok Sleman. Data were collected through interviews, documentation, questionnaire, notes, observation sheet, assessment sheet, and students' response. The descriptive analysis technique was used to analyze the data using rating methods. Results of the research show: (1) an assessment for learning through lesson study approach was successfully developed which consists of the assessment process and the product. Results of the assessment informs about students' processes in practice learning, product quality and overall practice results to determine students' achievement and also serves as formative feedback; (2) the effectiveness of the assessment, which was reviewed for eligibility, was categorized as